Identification and Characterization of Necroptosis-Related Differentially Expressed Genes in Acute Myocardial Infarction: Insights into Immune-Related Pathways and Protein-Protein Interactions: Necroptosis genes in heart attack - Zha, Yanping; Zhu, Tao; Li, Tian (Cellular and Molecular Biology, 2023)
Acute myocardial infarction (AMI) is a serious cardiovascular medical emergency that can lead to death. Necroptosis, a programmed cell death pathway, has been implicated in the development and progression of AMI. The aim of our study was to identify necroptosis-related differentially expressed genes (NRDEGs) in AMI and investigate their interactions and functions. The GSE66360 dataset was screened for NRDEGs using the 'limma' R package, with a threshold of p 0.05. A set of 159 necroptosis-related genes (NRGs) was retrieved from the KEGG database. The protein-protein interactions (PPI) network was constructed using the STRING data resource. Molecular Complex Detection (MCODE) and cytohHubba plugin was applied to find the major modules and genes. Gene ontology (GO) and KEGG pathway analyses were performed using the R ‘clusterProfiler’ package. The enrichment scores for immune cell types and associated biological pathways or functions were gained using the ssGSEA method. Our study identified 5 down-regulated and 16 up-regulated NRDEGs in AMI. The PPI network analysis revealed several important modules and hub genes, including TNF, IL1B, TLR4, STAT3, NLRP3, TNFAIP3, CYBB, IFNGR1, FADD, and IL33. GO analysis revealed that NRDEGs were enriched in multiple biological processes, cellular components, and molecular functions, including those related to cytokine production, response to cytokine stimulus, and necroptotic process. NRDEGs were found to be particularly abundant in a number of non-disease pathways, such as necroptosis and immune-related pathways like cytokine-cytokine receptor interaction and TNF signaling pathway, according to KEGG pathway analysis. The ssGSEA analysis revealed a correlation between immune cells and NRDEGs in AMI. The study identified NRDEGs and their interactions in AMI, providing insights into the potential function of necroptosis in the pathological process of AMI. The results imply that immune-related pathways and cytokines may be crucial in the initiation and development of AMI. The study provides a foundation for further research on the underlying mechanisms of necroptosis in AMI and the potential for developing novel therapies.